Gambaran proses perencanaan dan pengadaan kebutuhan farmasi di apotek farmarin dalam perspektif Islam - Nastiti, Nindita Sari; Amanda, Salsabila; Yanualisarani, Cahyani (Journal of Pharmaceutical and Sciences, 2025)
Medicines are a very important element in health care efforts, therefore the availability of medicines must always be guaranteed. Unsecured availability of medicines, or shortages of medicines in pharmaceutical facilities such as pharmacies, can result in lowering the level of consumer confidence. In an Islamic perspective, the need for medicine is included in maqashid al-dharuriyyat (primary needs) because it is related to preserving life or maintaining the soul (hifdz al-nafs). This research uses a descriptive method with a qualitative approach. Based on the research that has been carried out, it can be concluded that the planning and procurement process at the Farmarin pharmacy is in accordance with pharmaceutical service standards and is in accordance with the Islamic perspective, namely procurement at the Farmarin pharmacy using consumption methods and epidemiological methods and taking into account the halalness of medicines.